GE_GERICHTE C/11574/2016 vom 23. Januar 2017 - GE Cour de justice (2017)
ÉVACUATION(EN GÉNÉRAL) ; EXPULSION DE LOCATAIRE ; EXÉCUTION FORCÉE ; MODIFICATION DE LA DEMANDE | CPC.227.1; CPC.58.1; LaCC.30.4;